Desempenho Produtivo e Atividade Microbiana Cecal de Coelhos Alimentados com Dietas Contendo Diferentes Níveis de Amido - Varela De Arruda, Alex Martins; Carregal, Ronaldo Dessimoni [UNESP]; Ferreira, Renato Gonçalves [UNESP] (My University, 2000)
With the objective to evaluate the effect of dietary starch on the productive yield and cecal microbial activity for rabbits in the growing, four experimental diets were formulated to contain increasing corn starch levels (23, 28, 33 and 38 % total starch levels in dry matter basis). A total of 32 White New Zealand rabbits were allotted to finishing cages in a completely randomized block design. The results showed a decreasing linear effect for the feed intake and feed:gain ratio, where values of 108.67g/d and 3.216, respectively, were recorded for animals fed 38% dietary starch. However, no difference was observed for the weight gain and carcass yield. Regarding to cecal microbial activity, pH and volatile fatty acid production were not affected by the treatments, but the propionic acid concentration showed a decreasing linear effect, in such a way that higher molar proportion (12,06 %) was observed in the rabbits fed 23% dietary starch. The starch from corn grain showed higher effect on the cecal microbial activity that the purified corn starch, but did not change the performance and carcass yield.
Performance and Cecal Microbial Activity of Growing Rabbits Fed Diets with Different Starch Levels
Keywords: Feed:gain ratio; Nutrition; Rabbits; Starch; Volatile fatty acids